2021
DOI: 10.1093/ajhp/zxaa424
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a formal pharmacy residency research certificate program

Abstract: Purpose We describe the structure, implementation, and initial evaluation of a formal residency research certificate program (RRCP) designed to further advance residents’ knowledge and skills in research in an effort to better prepare residents for research involvement during their careers. Summary Pharmacy residency programs vary in the degree of emphasis on research education and training and the structure of resident resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Currently, literature investigating pharmacy educators’ experiences implementing a residency at a national level is limited. Most studies reported on the experience in single healthcare services and longitudinal observations on how experiences change over time are lacking [ 34 36 ]. They reported on localised challenges, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, literature investigating pharmacy educators’ experiences implementing a residency at a national level is limited. Most studies reported on the experience in single healthcare services and longitudinal observations on how experiences change over time are lacking [ 34 36 ]. They reported on localised challenges, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They reported on localised challenges, e.g. sustaining funding for resident and post residency positions, communication between supervisors to ensure a clear understanding of residents’ progress and the development of time management skills by residents [ 34 36 ]. In comparison, this study provides unique insights from educators over a longer period of time regarding a nationwide program.…”
Section: Discussionmentioning
confidence: 99%
“…Such development programs are highly variable, with a spectrum of time commitment, content, review, and practice opportunities. 18,19,[35][36][37][38][39] Program providers are variable and include residency preceptors, the site of the residency program, the college or school of pharmacy, local or national pharmacy organizations, and interprofessional organizations. Development programs may be free or may require purchase; thus, the choice of program may depend on residency funding capabilities.…”
Section: Previous Research Experiencementioning
confidence: 99%
“…Timing of the research program is also variable, with some occurring during residency orientation and others delivered at milestone points where learners receive the specific research knowledge needed as they begin or complete a step in the research process. Studies have shown improvement in resident confidence in completing research activities after completion of a research development program, 18,19,36,37 though a barrier to such training is balancing it with other required experiences.…”
Section: Previous Research Experiencementioning
confidence: 99%
“…Offering a formal research certificate with specific requirements that both the program and resident need to meet may help provide more focus and improved research experience for the resident. 10 As discussed by Morbitzer et al, increased collaboration within and between residency programs and schools of pharmacy can leverage expertise and share resources on resident projects. There needs to be more oversight and guidance provided to residents on how to conduct research.…”
Section: E D I T O R I a Lmentioning
confidence: 99%